2017
DOI: 10.1021/jacs.6b13275
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Isocyanides with Metal Carbyne Complexes: Isolation and Characterization of Metallacyclopropenimine Intermediates

Abstract: η-Iminoketenyl species have often been postulated as the intermediates in nucleophile-induced carbyne-isocyanide C-C coupling processes. However, such species are elusive. Here we report direct formation of η-iminoketenyl complexes from reactions of metallapentalyne with isocyanides. Our studies show that steric effects of N-substituents of the isocyanides play an important role in the stability of the three-membered metallacycles of the η-iminoketenyl complexes. Sterically bulky isocyanides, such as tert-buty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 57 publications
(21 reference statements)
1
26
0
Order By: Relevance
“…All the salient features of 1 compare well with those of previously reported aromatic osmapentalynes 39 . Osmapentalynes and related osmium chelates with multidentate carbon ligands have attracted considerable attention as novel aromatic molecules with unique properties, especially in the area of photophysics 39 43 , 48 . However, previous methods reported for the synthesis of these chelates with multidentate carbon ligands require the use of an unstable osmacycle precursor via standard Schlenk techniques 39 43 , 48 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the salient features of 1 compare well with those of previously reported aromatic osmapentalynes 39 . Osmapentalynes and related osmium chelates with multidentate carbon ligands have attracted considerable attention as novel aromatic molecules with unique properties, especially in the area of photophysics 39 43 , 48 . However, previous methods reported for the synthesis of these chelates with multidentate carbon ligands require the use of an unstable osmacycle precursor via standard Schlenk techniques 39 43 , 48 .…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, our research has focused on the construction of as many metal–carbon σ bonds as possible between a carbon ligand and a metal center, achieving a series of conjugated carbon-ligated multidentate chelates, termed carbolong complexes, with novel structures and unique properties 39 43 . All of these complexes contain three or more metal–carbon σ bonds; however, these metal–carbon σ bonds could only be constructed step by step.…”
Section: Introductionmentioning
confidence: 99%
“…For example, with sodium methanethiolate (under aC Oa tmosphere) 59 is obtained( Scheme 20). [19] Like metallapentalynes,t he metallapentalene derivatives have an eight-p-electron count and exhibit Mçbius aromaticity.F urther examples of the ambiphilic nature of the carbyne carbon in these metallapentalynes are given by the electrophilic addition of halogens [209] and the nucleophilic addition of isocyanides, [210] phenol [211] or anilines. [211,212] Unexpectedly,t reatment Concept of 57 with HBF 4 causes at automeric shift of the triple bond to give the closely related osmapentalyne 58,t hrough an isolable 16 e À metallapentalene intermediate.…”
Section: Metalla-analogues Of Classical Antiaromatic Compoundsmentioning
confidence: 99%
“…[1] Heterometallacycles as well as all-carbon metallacyclesw ith exocyclic heteroatoms can be accessed by using substrates and/orl igands such as CO 2 , [2] phospha-alkynes, [3] nitriles, [4] and isonitriles. [5] The versatility of isonitriles as ligandsw as thoroughly reviewed only recently. [6] We have demonstrated that isonitriles are versatile ligands fort he realisation of av ariety of coordination as wella sC ÀCa nd CÀNc oupling products at zirconocene and hafnocene fragments.…”
mentioning
confidence: 99%